Top Researchers May Suppress More Information Than They Provide: Surveying NBER Dismissive Literature Reviews - Richard P Phelps; Cathryn MacArthur (Nonpartisan Education Review)
The authors read a systematic sample of “working papers” downloaded from the website of the National Bureau of Economic Research (NBER) from the past quarter century—the years 2000 to 2024. They looked for “dismissive literature reviews” in the introductory and concluding sections of the papers. A dismissive review is one declaring an absence of previous research, or previous research worth referencing, for example: “there is no previous research on,” “this is the first study of,” and “surprisingly, few studies have broached this topic.” Typically, dismissive reviews are raw declarations, made without mention or evidence of having conducted a literature search. All working papers retrieved for the topic “education” are classified into three groups (lacking a true education focus, containing no dismissive reviews, containing one or more). The authors provide summary descriptive statistics for various quantities by category and a 1000+ line list of all the working papers retrieved and the dismissive reviews we found, which are highlighted within verbatim text. Dismissive reviews’ character and variety are discussed along with their implications for public policy.